Oral Health-Related Quality of Life in Chinese Children With Orofacial Cleft. (August 2020) - Lin, Jiu; Fang, Xinyi; Ha, Pin; Fu, Min; Wang, Hang
Objective: To measure the validity and reliability of a Chinese version of Child Oral Health Impact Profile (COHIP) and to assess oral health-related quality of life (OHRQoL) with regard to gender, age, and cleft types in Chinese children with orofacial cleft (OFC). Design: A total of 120 patients with OFC (8-15 years old) and their parents were investigated with COHIP in the West China Hospital of Stomatology. Items were divided into oral symptoms, functional well-being, emotional well-being, school, and peer interaction subscales, and scores on all subscales were compared between and within groups. Results: The internal consistency measured by Cronbach α was satisfactory in children's sample (0.85) and parents' sample (0.90). The correlation between children's and parents' questionnaires was moderate to weak (Pearson r = 0.34), which was also supported by moderate intraclass correlation coefficients. The OHRQoL of children differed significantly from parents on the overall COHIP, functional well-being, emotional well-being, and school subscales. Older children had poor OHRQoL, functional well-being, and emotional well-being. Girls had poor emotional well-being. Children with cleft lip and palate and cleft palate performed worse on the overall COHIP, functional well-being, and school subscales. Parents, boys, and younger children had better treatment expectations and global health perceptions. Conclusion: The Chinese version of COHIP is a reliable and valid tool to assess OHRQoL in Chinese children with OFC. Parents' reports could not replace children's answers but add complementary information. Children's gender, age, and cleft types should be considered in OHRQoL assessment and individual treatment plan.